Kemampuan Komunikasi Matematis Mahasiswa dalam Pembelajaran dengan Alqurun Teaching Model (ATM) - Utami, Lintang Fitra; Sutiarso, Sugeng; Suryadinata, Nurain; Hardianti, Desrina (Jurnal Pendidikan Matematika Universitas Lampung, 2025)
Mathematical communication ability is the skill of conveying mathematical thinking expressed in various forms of representation such as narratives, images, diagrams, videos, sounds and other media. Alqurun Teaching Model is an innovation in education in the form of a learning model that is designed to encourage students to improve their mathematical abilities, one of which is mathematical communication ability. The study aims to measure the difference in mathematical communication skills of students taught with Alqurun Teaching Model and conventional models. This research is a quantitative research with postest only control group design. Data were collected through tests designed to measure mathematical communication skills, then the results were analyzed using independent sample t-test. The sample involved was 85 students who were divided into two research groups, namely control and experimental classes. The sampling technique used purposive sampling technique where the sample was selectively chosen based on certain criteria, namely the same level of communication skills and facilitated with the same teacher and has a stable cognitive development so that it can interpret its mathematical ideas. The results showed that the mathematical communication skills of students subjected to the Alqurun Teaching Model were significantly superior to students subjected to conventional models.